LANGUAGE AND SPEECH. RESEARCH OF THE ISSUE OF SPEECH UNITS - Ochilova Gulnoza Farxod qizi (Innovate Conferences, 2025)
This article will describe scientific views on language and speech. The distinction between language and speech phenomena is analyzed. This article provides scientific research findings, interconnection and relationship between language and speech. In addition, some of the scientific views related to speech units are presented.
Keywords: language, speech, units of language, units of speech, differentiation, scientific views.